Manajemen Supervisi Akademik Terhadap Kinerja Guru pada Masa Pandemi Covid-19 - Teguh Prayitno (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
The purpose of this study was to study and analyze the management of Academic Supervision on Teacher Performance during the Covid-19 Pandemic. The research location is in Sekolah Aliyah Negeri 2 Bandung. This research is a research using a qualitative approach and the results of the research are presented in a descriptive form. Data collection in this study was carried out by means of interviews, observation, and documentation. The results showed: First, the Academic Supervision Management at SMP Negeri 2 Cimenyam Kabupaten Bandung for several components is in accordance with the theory of the implementation of covid academic supervision, namely (1) Planning: includes review of supervision programs, identification of infrastructure, preparation of assessment instruments, program synchronization and socialization program. (2) implementation: includes pre-observation activities (initial planning, checking learning plans, learning media), conducting online learning observations through media / applications, and conducting post-observation activities by analyzing the results of observations, evaluating and planning follow-up supervision (3) Evaluation: includes the activity of analyzing the results of the implementation of supervision from beginning to end and following up on the results of the supervision. Second, the teacher's performance in making learning planning is quite good, some components still need to be improved, and for the assessment of learning implementation, it has not been maximally carried out,the new assessment is seen when there is a report on learning activities by the teacher.